2013
DOI: 10.3928/01484834-20130819-02
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quality and Safety Education for Nurses (QSEN)–Related Student Experiences During Pediatric Clinical and Simulation Rotations

Abstract: Nurse educators are challenged with providing meaningful clinical experiences for students. However, patient safety regulations constrain what nursing students are able to accomplish in the pediatric setting. So, what are students actually doing in their clinical rotation? This pilot observational study was undertaken to provide a snapshot of the experiences available to nursing students that develop the six Quality and Safety Education for Nurses (QSEN) competencies. Students were directly observed during ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…The post simulation student survey [15] results suggested that students had higher confidence in their skills after simulation experiences. This conclusion confirmed previous studies [16] where students also reported a rise in confidence after implementing simulation.…”
Section: Discussionsupporting
confidence: 92%
“…The post simulation student survey [15] results suggested that students had higher confidence in their skills after simulation experiences. This conclusion confirmed previous studies [16] where students also reported a rise in confidence after implementing simulation.…”
Section: Discussionsupporting
confidence: 92%
“…Not all competencies were integrated equally; patient–centered care and safety were incorporated most frequently. This finding confirms the results reported in a pilot observational study by Pauly-O’Neill et al (2013). They investigated whether simulation settings offered opportunities to practice the six QSEN competencies and demonstrated that evidence-based practice, quality improvement, and informatics were more difficult to integrate.…”
Section: Discussionsupporting
confidence: 84%
“…Of these, six were based on course content. Seven instruments were developed to evaluate QSEN KSAs in a clinical/simulation setting (Altmiller, 2017; Leighton et al, 2015; Pauly-O’Neill et al, 2013; Piscotty et al, 2011; Poore et al, 2018; Tanz, 2018). One was developed in Sweden to evaluate the representation of QSEN competencies in clinical evaluation instruments used by nursing instructors (Nygårdh et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Students want to transfer learning to the workplace and new situations and must "demonstrate their learning in authentic contexts for workplace readiness" [6]. In most states, simulation is not accepted as a substitute for clinical experience, although this has been studied [7] [8].…”
Section: The Online Program and The Unique Challenges For Clinical Prmentioning
confidence: 99%